Antibiotic use to the production performance of ISA brown layer - Rahman, Md Khalaydur; Majumder, Md Kamrul Hasan; Ali, Md Yousuf; Khatun, Most Mahfuja; Kabir, Sarkar Enayet; Sakib, Md Nazmus; Islam, Mohammed Sirajul; Akter, Most Sumona; Sultana, Fowzia (Asian Journal of Medical and Biological Research, 2017)
The present study was designed with a view to study the effects of enrofloxacin antibiotic on ISA brown layer performance. A total of 1,80,000 laying hens (ISA brown) received and supplied enrofloxacin antibiotic in the dose of 0 mg, 10mg and 20 mg/kg BW with normal diet. Each layer was fed 120 g feed/day from 42 to 48 weeks of age. Antibiotic made significant differences in egg production (p<0.05) and especially on mortality (p<0.01). The different doses of enrocin (0 mg, 10mg and 20mg/kg BW) had no significant effect on feed conversion efficiency and egg weight. Therefore, it can be suggested that a lower dose (10mg/kg BW) of antibiotic may be benefited in commercial layer diet. Asian J. Med. Biol. Res. December 2016, 2(4): 541-546